Formy przemocy wobec kobiet w Pakistanie - Kiezik, Julia (Katedra Doktryn Politycznych i Prawnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2022)
Pakistan is a party to the International Covenant on Civil and Political Rights, as well as to the Convention on the Elimination of All Forms of Discrimination Against Women. Nonetheless, the country is considered to be one of those respecting the fundamental women’s rights in the least. Non-governmental organizations such as Amnesty International and the Human Rights Commission of Pakistan are in agreement regarding the alarming situation of the safety of Pakistani women who fall victims to crimes against their lives and health every day. The acts of violence they experience are a form of punishment for the activities considered shameful or at least inappropriate in the eyes of the society. The significant amount of these acts is dictated by the patriarchal perception of women and their duties related to men. The article analyses the forms of violence against women such as dowry punishments, acid attacks, and honour killings in the light of the Pakistani law and the Islamic culture. The author aims to explain the reasons for the crimes and the serious consequences for the victims’ future, and examines the legislature, the law enforcement and the traditional patriarchal values in Pakistan, playing a key role on the society’s approval for the ongoing violence.
Keywords: Pakistan; women’s rights; gender-based violence; acid attacks; dowry; honour killings